Attitudes toward COVID-19 vaccines during pregnancy and breastfeeding - Simsekoglu, Nesibe; Akyuz, Enes; Guven, Rabia; Pasin, Ozge (Frontiers in Public Health, 2024)
Background: Although vaccination is one of the most effective means of controlling the spread of COVID-19, public concerns and indecision about vaccination still continue. Because pregnant and breastfeeding individuals are at high risk for severe outcomes in case of infections, determining their level of hesitation and attitude toward COVID-19 vaccines will guide the management of the disease. This study aimed to determine pregnant and breastfeeding women's levels of hesitation and attitude toward COVID-19 vaccines as well as their related factors. Methods: The sample of this descriptive research consisted of 103 pregnant or breastfeeding individuals who were seen at the obstetrics and gynecology outpatients clinic of a state hospital in Istanbul, Turkey. The data were collected using a ‘demographic data form’, the ‘Vaccine Hesitancy Scale in Pandemic’, and the ‘Attitudes toward COVID-19 Vaccine Scale’. The research data were analyzed with appropriate statistical methods. Results: The mean age of the participants was 29.71±4.75, 51% were pregnant. The mean score of the ‘Vaccination Hesitancy Scale in Pandemic’ was 30.83±6.91, and the mean score for the ‘Attitude Scale toward the COVID-19 Vaccine’ was 25.50±5.20. A significant difference was found between the total score of the ‘Vaccine Hesitation Scale in the Pandemic’ and the mean score of the 'Lack of Confidence' sub-dimension between the 'working status' and the 'influenza vaccination' status. In terms of the mean score of the 'Risk' sub-dimension, a significant difference was found between the 'period of vaccination' (p<0.05). According to the mean total score of the ‘Attitude Towards COVID-19 Vaccine Scale’, there was a significant difference between the 'smoking' status. There was a significant difference in the 'Positive Attitude' sub-dimension in terms of the 'flu vaccination' status. There was a significant difference in the 'Negative Attitude' sub-dimension in terms of the 'chronic disease' status. A positive correlation was found between the total scores of the scales. Conclusions: It was concluded that although the participants had a high level of hesitation towards the COVID-19 vaccine, they had a positive attitude. The results obtained will be guided in determining the strategies to be developed for these specific groups in future pandemics.